The influence of internal control, organizational culture and financial pressure on fraud with ethic egoism as a moderation - Sastrawan, Randi; Mediaty; Amiruddin (International Journal of Multidisciplinary Research and Studies, 2022)
This study aims to examine internal control, organizational culture and financial pressure on fraud with ethical egoism as a moderator. This research was conducted at the Office of the Agriculture Office of North Luwu Regency with a research time ranging from two months, starting from October 2022 to November 2022. This research uses quantitative research methods. This study uses primary data collected by conducting direct research in the field, by giving questionnaires/statement sheets to 72 respondents. The statistical method used to test the hypothesis is multiple linear regression. The results showed that internal control and organizational culture had a negative effect on fraud, and different things were produced by financial pressure which had a positive effect on fraud. Whereas in the moderation effect in this study, ethical egoism weakens the effect of internal control and organizational culture on fraud and strengthens the effect of financial pressure on fraud.